On a new one parameter generalization of Pell numbers - Bród, Dorota (Annales Mathematicae Silesianae, 2019)
In this paper we present a new one parameter generalization of the classical Pell numbers. We investigate the generalized Binet’s formula, the generating function and some identities for r-Pell numbers. Moreover, we give a graph interpretation of these numbers.